Open sandwich fluorescence-linked immunosorbent assay for detection of soy isoflavone glycosides. (1st November 2021) - Sakamoto, Seiichi; Uchiyama, Hiroki; Yusakul, Gorawit; Kyokong, Napat; Pongkitwitoon, Benyakan; Putalun, Waraporn; Tanaka, Hiroyuki; Morimoto, Satoshi
Highlights: Open sandwich system was firstly applied to fluorescence-linked immunosorbent assay. AcGFP1-VH were superior to VH-AcGFP1 as a probe for os-FLISA. Detectable range for DZ and GEN in os-FLISA exhibited 0.1–12.5 µg mL −1 . os-FLISA was applied to determination of soy isoflavone glycosides, DZ and GEN. Abstract: To detect major soy isoflavone glycosides, namely daidzin (DZ) and genistin (GEN), novel open sandwich fluorescence-linked immunosorbent assay (os-FLISA) was developed by taking advantage of enhanced interactions between variable regions of heavy (VH) and light chain (VL) domains in the presence of an antigen. The VH and VL genes were expressed in Escherichia coli as a chimera protein with green fluorescence protein (AcGFP1) and maltose-binding protein (MBP), respectively. Comprehensive characterization of os-FLISA displayed nearly the same specificity as parental DZ- and GEN-specific monoclonal antibody, demonstrating the potential of the developed assay for detection of both DZ and GEN. Their detectable range in this system exhibited at 0.1–12.5 μg mL −1 . Subsequent validation analysis revealed that os-FLISA was reliable and accurate system for detection of total soy isoflavone glycosides. Notably, this is the first FLISA based on an open sandwich system, which can be employed for the detection of small molecules.